Selective absorption of swelling rubber in hot and warm asphalt binder fractions. (30th March 2020) - Yu, Huayang; Leng, Zhen; Zhang, Zeyu; Li, Danning; Zhang, Junhui
Graphical abstract: Highlights: The asphalt-rubber interacting area was obtained by staged extraction method. The swelling rubber incline to absorb components of smaller molecular size. Polymers with CO bond were absorbed limitedly by swelling rubber. The absorption behaviors of swelling rubber promote the rutting resistance. The effects of WMA additives on absorption preference were evaluated. Abstract: The use of waste tire rubber as asphalt modifier has been a practice-ready technology. However, the interaction among components within asphalt rubber (AR) and warm asphalt rubber (WAR) is still unclear. During the blending process, the swelling rubber releases polymer agents in asphalt and absorbs components from both asphalt and warm mix asphalt (WMA) additive simultaneously. The component interaction significantly influences the final rheological properties. A comprehensive understanding of the selective absorption of crumb rubber during the blending process provides references to optimize the material and procedure design of rubberized asphalt. To this end, one AR and two WARs were prepared with three mixing durations. The liquid phases and crumb rubber particles were separated. The separated swelling rubber particles were then processed by the staged extraction method to divide the asphalt-rubber interacting area from outside to inside into four layers. The absorption preference of swelling rubber and its influence on rheological properties were investigated by chemical and rheological tests. Test results showed that asphalt fractions with smaller molecular weight were absorbed into deeper layers of swelling rubber. By contrast, crumb rubber was found to be reluctant to absorb the fractions with CO bond during the mixing process. In addition, the Fischer Tropsch (FT) wax showed a negligible influence on the absorption preference, while the effect of surfactant on absorption preference was significant. Finally, the relationship between absorption preference and rheological properties was established. It was found that the absorption preference of crumb rubber is beneficial to the rutting resistance of rubberized asphalt.